2007
DOI: 10.1086/520029
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications of Open Type III Tibial Fractures among Combat Casualties

Abstract: Background. Combat is associated with high-energy explosive injuries, often resulting in open tibial fractures complicated by nonunion and infection. We characterize the infections seen in conjunction with combat-associated type III tibial fractures.Methods. We performed a retrospective medical records review to identify US military service members Results. Of the 62 patients with open tibial fractures who were identified in our initial search, 40 had fractures that met our inclusion criteria as type III diaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(150 citation statements)
references
References 20 publications
8
134
0
1
Order By: Relevance
“…On repeat culture, A. baumannii was not isolated in any patients after 6 to 8 weeks of broad spectrum antibiotics targeting MDR AB. In at least four of these patients, SA, but no A. baumannii was isolated when deep cultures were performed 2 to 15 months later [11]. A retrospective chart review concluded that initial episodes of combat-related osteomyelitis from the upper and lower extremities were more likely to be polymicrobial than monomicrobial.…”
Section: Discussionmentioning
confidence: 95%
“…On repeat culture, A. baumannii was not isolated in any patients after 6 to 8 weeks of broad spectrum antibiotics targeting MDR AB. In at least four of these patients, SA, but no A. baumannii was isolated when deep cultures were performed 2 to 15 months later [11]. A retrospective chart review concluded that initial episodes of combat-related osteomyelitis from the upper and lower extremities were more likely to be polymicrobial than monomicrobial.…”
Section: Discussionmentioning
confidence: 95%
“…As survivorship has increased, even among patients with devastating extremity wounds that would have been fatal in the past, multidrug-resistant pathogens are complicating recovery [78]. A major concern is that past ill-advised use of broad-spectrum antibiotics for empirical treatment of combat wounds is resulting in selection of more resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similarly, infection is the most common cause of delayed amputation in combat-related open tibial fractures. 2 Bacteria produce biofilm that is protective against microbial agents, 3 and the antibiotic concentrations needed to eliminate these sessile colonies found in biofilms can be more than 500 times those required to kill planktonic bacteria. 4 The high doses of systemic antibiotics that are above the minimum inhibitory concentration required at the fracture site may cause systemic toxicity.…”
mentioning
confidence: 99%